2021
DOI: 10.1016/j.clnu.2021.08.020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of plasma vitamin C levels on the risk of cardiovascular diseases and Alzheimer's disease: A Mendelian randomization study

Abstract: Background & aims: Previous observational studies have reported associations between plasma vitamin C levels, and cardiovascular diseases (CVDs) and Alzheimer's disease (AD); however, no conclusive results have been obtained. We conducted a Mendelian randomization (MR) study to investigate the causality of vitamin C on the risk of nine CVDs [including coronary artery disease (CAD), myocardial infarction (MI), atrial fibrillation (AF), heart failure (HF), stroke, ischemic stroke (IS), and IS subtypes] and Alzhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Previous MR using serum antioxidants as exposures also showed similar results. For example, serum vitamin C was not associated with multiple cardiovascular diseases [44,47,48]; other antioxidants (vitamin E, carotene, lycopene and retinol) were not associated with risk of ischemic stroke [49] and CHD [50].…”
Section: Discussionmentioning
confidence: 99%
“…Previous MR using serum antioxidants as exposures also showed similar results. For example, serum vitamin C was not associated with multiple cardiovascular diseases [44,47,48]; other antioxidants (vitamin E, carotene, lycopene and retinol) were not associated with risk of ischemic stroke [49] and CHD [50].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, F statistics ( Eq. (1) ) were used to test the strength of the association between the SNPs as instrumental variables and tea consumption, and an F statistic >10 indicates a lower risk of weak instrumental variable bias ( Zhang Q. et al, 2021 ; Chen et al, 2021 ). N represents the sample size; eaf represents effect allele frequency.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps the most interesting studies are those assessing causality using blood biomolecules as these are easy biomarkers to capture for stroke risk assessment but can also be potential drug targets. Not all the studies to date have observed causal associations with stroke risk, in either direction (inflammatory biomarkers [ 76 , 77 , 79 , 83 ], between circulating cytokines [ 96 ], vitamins [ 78 , 79 , 80 , 81 , 82 , 83 , 114 ], and many polyunsaturated fatty acids [ 70 ]). Some interesting findings are: (1) the identification of a causal link between lower serum MMP-12 levels and the risk of AIS, lower serum MMP-1 and MMP-12 levels and the risk of LAS, and higher serum MMP-8 levels and the risk of SVS [ 94 ]; (2) genetically determined levels of hemostatic factors have also been associated with the risk of IS [ 87 , 88 ]; (3) iron factors are causally associated with an increased risk of IS and CES, except transferrin, which is protective against IS and CES [ 73 ]; (4) among the cytokines studied, monocyte chemoattractant protein-1 (MCP-1) is the only one that was associated with an increased risk of IS, LAS, and CES [ 96 ].…”
Section: Mendelian Randomization In Strokementioning
confidence: 99%